Determinants of FDI from Taiwan to the UK - Chu, Ming-Ching (2006)
The main objective of this research is to identify factors influence foreign investment from Taiwan to the UK. The result of empirical study is established on the information obtained from the survey and prior studies in this field. Following, we employ the theoretical background to evaluate empirical FDI behaviour of Taiwanese firms into the UK. Moreover, the overview of the FDI pattern from Taiwan to the UK is being appraised for capturing the whole picture of Taiwan's FDI to Europe. By comparison of patterns of southeast countries and European nations, the debate is discussed in the analysing section. The study outcome of the research is as follows: The chief components determining FDI are market size, market growth in the host nation, human-resource endowment and economic-political environment. Furthermore, the pattern that Taiwanese firms invest in the UK is different from that in southeast countries. Additionally, by providing a friendlier investment environment to foreign investors UK can enhance FDI activities. In a word, the UK nation plays an important and irreplaceable role to Taiwanese firms and the rest of the world for the FDI action.